Reaksi Pasar Modal Terhadap Pengumuman Resesi Ekonomi Indonesia Tahun 2020: Studi Kasus Pada Perusahaan Yang Terdaftar di JII - Elok Karerina; Bagas Arya Wiguna; Ahmad Ilham Suhaemy (JIEF : Journal of Islamic Economics and Finance, 2021)
This study aims to determine the reaction of the stock market 5 days before and 5 days after the announcement of the economic recession in Indonesia on November 5, 2020 to abnormal returns. The approach used is quantitative with the event study technique. The model used to see the Average Abnormal Return (AAR) is a market model with a research period of 80 days before observation and a research period of 5 days before and 5 days after the announcement. This study used a purposive sampling technique to obtain a sample of 29 companies registered in the Jakarta Islamic Index (JII). This study found that there was no significant difference between the Average Abnormal Return (AAR) 5 days before and 5 days after the announcement of the economic recession in Indonesia on November 5, 2020.